Accuracy of sonographic estimation of weight in fetuses with abdominal wall defects. (14th April 2020) - Spaulding, Portia; Edwards, Andrew; Coombs, Peter; Davies‐Tuck, Miranda; Robinson, Alice
Abstract : Background: Accurate estimation of fetal weight is essential in guiding management of fetuses with abdominal wall defects (AWDs), as growth restriction is an important predictor of perinatal morbidity and mortality. Several sonographic formulae are available involving multiple biometric parameters, but abdominal circumference measurements may underestimate weight in fetuses with AWDs. No formula has yet shown superior accuracy. Aims: The objectives of this study were to evaluate, in fetuses with gastroschisis and omphalocoele, the accuracy of a sonographic estimated fetal weight (EFW) formula proposed by Siemer and colleagues, specifically for use in fetuses with AWDs compared to the commonly used Hadlock IV formula in estimating fetal weight, and detecting small for gestational age (SGA) fetuses. Materials and Methods: A retrospective cohort of 113 fetuses with AWDs was identified from an Australian teaching hospital over 13 years. Pregnancy data and sonographic fetal biometry parameters were obtained. The accuracy of each formula in predicting birthweight was compared using Bland–Altman limits of agreement, and the intraclass correlation coefficient between EFW and actual birthweight. Performance of each formula in detecting SGA fetuses was determined. Results: The Siemer and Hadlock formulae have similar accuracies for predicting birthweight in fetuses with AWDs. The Hadlock formula has a higher detection rate for SGA < 10 th centile and < 3 rd centile compared to the Seimer formula (84% vs 68% and 83% vs 67% respectively), albeit with a higher false‐positive rate. Conclusion: There is no clear clinical advantage in using the Siemer formula, which is specifically designed for fetuses with AWDs, over the Hadlock formula to estimate weight in fetuses with AWDs.